KIPRAH DAN DAYA TARIK BAMBANG SP SEBAGAI MAESTRO KARAWITAN JAWATIMURAN - Muhammad, Anbie Haldini; Simatupang, G.R. Lono Lastoro; Mulyana, Aton Rustandi (Institut Seni Indonesia (ISI) Surakarta, 2020)
Bambang Sukmo Pribadi or known as Bambang SP is a developer-maestro of karawitan Jawatimuran. The record of maestro was found in International Gamelan Festival 2018, Surakarta. A maestro title is not something easy to earn, however it’s also need to be known particularly in which extent Bambang SP’s attraction as a maestro in karawitan Jawatimuran. Bambang SP has a few covered record as a maestro and the discourse of karawitan Jawatimuran also not widely known especially in karawitan Jawatimuran community. The aim of this study is to explore constellation paradigm between Bambang SP and karawitan Jawatimuran. This paper is describing how Bambang SP’s creativity expands karawitan Jawatimuran. This practice holds conclusion of the use of karawitan Jawatimuran’s idiom at any expanding works as Bambang SP’s innovation. In the other hand, Bambang SP doesn’t leave the existence of traditional art in karawitan Jawatimuran. This attractiveness indirectly followed by his fellows as well as next generations.